Optimized synthesis and characterization of red-shifted nitrogen-doped carbon quantum dots for highly sensitive detection of Fe3+ ions in aqueous media - Kamaruzaman, Nur Afif Nadhrah; Fadzil, Nadia Izati; Alli, Yakubu Adekunle; Tan, Tongling; Abdullah, Jaafar; Rashid, Suraya Abdul (Elsevier, 2025)
The development of environmentally friendly, cost-effective, and highly sensitive fluorescent nanomaterials remains a significant challenge for applications in metal ion detection. Conventional carbon quantum dots (CQDs) often suffer from limited emission tunability and low quantum yield, restricting their performance in sensing applications. In this study, red-shifted carbon quantum dots (R-CQDs) and red-shifted nitrogen-doped carbon quantum dots (R-NCQDs) were successfully synthesized via a facile hydrothermal method using empty fruit bunch (EFB) biochar as a carbon precursor and urea as a nitrogen source. The effects of solvent concentration (4.3–10.3 M aqueous sulphuric acid), urea dosage (0.2–1.0 g) and the temperature (170–210 °C) were investigated for their influence on the energy band gap of R-CQDs and R-NCQDs. The synthetic procedure was optimized using response surface methodology (RSM) based on a central composite design (CCD). The structural and optical properties of the synthesized R-CQDs and R-NCQDs were characterized using UV-Vis spectroscopy, photoluminescence spectroscopy, X-ray diffraction (XRD) and HR-TEM. Under excitation at 360 nm, R-CQDs and R-NCQDs exhibited maximum fluorescence emissions at 450 and 470 nm with the quantum yield of 58 % and 61 %, respectively. The hydrophilic optical properties of the synthesized R-NCQDs were effectively utilized to detect Fe3+ ions with good selectivity and sensitivity. The fluorescence of R-NCQDs was significantly quenched in the presence of Fe³ ⁺ ions in an aqueous medium. The quenching rate showed a linear correlation with increasing Fe³ ⁺ concentration, demonstrating a low detection limit of 0.19 μM and a broad detection range of 0–300 μM. This study highlights the potential of R-NCQDs as a fluorescence-based sensor for metal ion detection while also providing valuable insights into the properties and molecular structure of R-NCQDs, achieved through a simple and efficient synthesis approach.